2020
DOI: 10.1111/php.13289
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Photoprotective Compounds of a Phenolic Nature in the Response of Arabidopsis Thaliana Leaf Tissues to Low‐Intensity Laser Radiation

Abstract: The influence of low‐intensity laser radiation (LILR) on the changes in the content of anthocyanins, kaempferol, quercetin and their glycosides in the leaves of 5‐week‐old plants of Arabidopsis thaliana L. was studied by means of methods of high‐performance liquid chromatography and gas chromatography mass spectrometry (GC‐MS). It was found that in the leaves subjected to a stimulating He‐Ne laser radiation dose (3.6 J cm−2, continuous wave radiation, wavelength—632.8 nm, exposure time—5 min), the radiation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…On the other hand, photoprotection of phenolic compounds is related to the capture of free radicals formed in the mitochondria, chloroplasts, vacuoles, apoplasts, and peroxisomes [58,59]. They constitute a 'secondary' antioxidant system that is activated as a result of a decrease in the activity of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, photoprotection of phenolic compounds is related to the capture of free radicals formed in the mitochondria, chloroplasts, vacuoles, apoplasts, and peroxisomes [58,59]. They constitute a 'secondary' antioxidant system that is activated as a result of a decrease in the activity of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the results suggested the TF, TP, PAC, and ACs content of blueberry increased with altitudes rising from 37 to 2,010 m. This could be due to the plant's protective mechanisms against the stronger solar radiation and ultraviolet light generally prominent in high altitude regions (Jaakola et al, 2004;Zoratti et al, 2015). Such strong radiation and ultraviolet light could increase free radicals, such as reactive oxygen species (ROS), which activate the biosynthesis of flavonoids, especially anthocyanins to protect plant organs (Dudareva et al, 2020).…”
Section: Phytochemical Compounds Of Blueberry Affected By Growing Locmentioning
confidence: 96%
“…weeds in the test area and the dry weight of weeds in the blank region without laser irradiation (Dudareva et al, 2020;Rani et al, 2022).…”
Section: Validation Of Blue Light Laser Weed Controlmentioning
confidence: 99%